SENI BELUK PRESERVATION IN CIKONDANG INDIGENOUS VILLAGE REVIEWED FROM THE PERSPECTIVE OF MUSIC EDUCATION - Cipta, Febbry; Gunara, Sandie; Sutanto, Toni Setiawan (Humaniora, 2020)
The research was conducted to develop a music model based on local wisdom. Through this article, researchers at Cikondang village, Pangalengan, West Java. The research problem was that, along with the changing times, the next generation tended to ignore the values of local wisdom. So that through music learning, the values of art could be understood and actualized in everyday life. Music (nembang and ngabeluk) became a medium to express values in pupuh verses, which contained wawacan about the relationship between man and their God; man and others; and man and their surroundings. The data collection was done using observation, interview, and literature review then analyzed with the music education approach. The obtained results reveal that the learning process of seni beluk in Cikondang Village has taken place in the context of community education, which is done informally, and formed naturally. There is no invitation or coercion from the elders to the next generation to learn this art form. Meanwhile, for people from the next generation who has a passion for learning, the learning steps do not only train their techniques, but they also learn about the values ingrained in the pupuh verses.